Optimal Blood Pressure in the Hypertensive Patient and the J-Curve Dilemma - Sinclair, Heather Q. (MD Conference Express, 2010)
The benefits of antihypertensive drugs vary by therapeutic strategy, and the search continues for optimal treatment. While guidelines have been developed to manage hypertension (HT), research continues to emerge that occasionally conflicts with current recommendations. Despite progress being made in the area of HT research, many questions remain unanswered. This article discusses recent data from clinical trials and how they pertain to current hypertensive treatment strategies, as well as trial needs moving forward.